PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI UMUM (DAU) TERHADAP PDRB DENGAN BELANJA MODAL SEBAGAI VARIABEL MEDIATING (Studi Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2013 – 2015 - Vivi Dela Safindah, 14.05.52.0252; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2018)
The objective of this research was to analyze the effect of capital expenditure in mediating the relationship between Regional Generated Revenues and General Allocation Fund to the economic growth as measured by the Regional Gross Domestic Product (PDRB). Secondary data of those variables were collected from 35 regency/municipality in Central Java Province for the period of 2013 to 2015. Analysis technique using by path analysis.The results of the research showed (1) there is a positive influence and significant Regional Generated Revenues effect on capital expenditure, (2) there is a positive influence and significant General Allocation Fund effect on capital expenditure, (3) there is a positive influence and significant Regional Generated Revenues effect on economic growth (PDRB), (4) there is a positive influence and significant General Allocation Fund effect on economic growth (PDRB), (5) there is a negative influence and did not significant capital expenditure effect on economic growth (PDRB),(6) the variable capital expenditures are not proven to mediate the influence of Regional Generated Revenues effect on economic growth (PDRB),(7) the variable capital expenditures are not proven to mediate the influence of General Allocation Fund effect on economic growth (PDRB).Keywords: Regional Generated Revenues, General Allocation Fund, Capital Expenditure, Economic Growth, Regional Gross Domestic Product (PDRB)